Giving Questions as Scaffolding to Help Student in Constructing Proof - Nurul Laili; Tatag Yuli Eko Siswono (Universitas Muhammadiyah Surabaya, 2020)
This research deals with the challenge of helping student who has difficulty in constructing trigonometry proof. This qualitative research that describing scaffolding process using questions involves 20 students in second grade of senior high school, then selects a student from the 11 students who cannot solve the proof completely. Student’s work on proving test and interview recording are collected and analysed data to identify student’s difficulty, type of scaffolding to help, and development produced. This research points out the difficulty student faces are: difficulty in devising strategy, stuck in the process, unable to find the next step, and unable to find relation between two terms. Scaffoldings given are: asking the characteristic of what to be proven, asking a concept that may be used, directive question, facilitative utterance, trans active prompt and bridging analogy. Furthermore, developments produced from scaffolding given are: student can purpose new idea and strategy, can find relation between two things or two concepts, and student can determine and use appropriate concept.